THE ROLES AND PROBLEMS OF RETIRED TEACHERS: A CASE STUDY WITH SPECIAL REFERENCE TO SELECTED VILLAGES IN EASTERN SRI LANKA - Ayoob, S.M.; Mahir, I.L.M. (International Journal of Psychosocial Rehabilitation, 2020)
Human society has evolved and run through the exchange of knowledge from one another. Therefore, it is believed that teaching is one of the most valuable professions in the world. Retirement of the teachers brings both positive and negative outcomes. And the retired teachers play significant roles in the society and on the other hand they face numerous problems too. In this regard, this study was carried out among retired teachers from selected villages in Ampara and Batticaloa districts. Primary data were collected mainly through questionnaire, focus group discussions, case studies and key informant interviews. The study identified that the retired teachers played immersive and immersive role by involving in enthusiastic activity, provide financial assistance, working with school development society, teaching. Further considerable amount of retired teachers takes the role of leadership and involve in literary activities. The study also identified the problems of retired teachers related with finance, school and society.